Application of aqueous two-phase systems in the recovery of cyclodextrin glycosyltransferase and cyclodextrins - Ng, Hui Suan (2013)
Cyclodextrin glycosyltransferase (CGTase, 2.4.1.19) is an extracellular hydrolytic enzyme which capable to convert starch into cyclodextrins (CDs) via cyclization activity. CDs are cyclic oligosaccharides consisted of six or more glucose units which are widely applied in various industries owing to their unique structure of hydrophobic inner cavity and hydrophilic exterior, which enable the CDs to form inclusion complexes with a variety of guest molecules. The purpose of this study was to introduce an effective approach on the recovery of CGTase from newly isolated Bacillus cereus fermentation broth and CDs from production media by reducing time and steps involved in the purification and recovery processes. Aqueous Two Phase Systems (ATPSs) were applied for the recovery of CGTase and CDs to simplify the downstream processing of CGTase. Basic polyethylene-glycol (PEG)/ citrate ATPS was performed to capture the enzyme CGTase from fermentation broth. Several ATPS parameters such as tie-line length (TLL),molecular weight of PEG, volume ratio (VR), crude load and addition of neutral salt were investigated and optimized in order to obtain the most effective ATPS for the CGTase recovery. Partial purification of B. cereus CGTase with yield (YT) of 70% was achieved on the 19.0% PEG and 11.5% citrate ATPS with TLL of 38.89% (w/w),VR of 2.0, 20% (w/w) crude load and additional 4% (w/w) NaCl at pH 7.0. The recovery of CGTase by ATPS was then improved by developing a recyclable ATPS in which the polymer PEGs were substituted by using copolymer, ethylene oxide-propylene oxide (EOPO). The capability of EOPOs to separate into two phase after heating above certain temperature enables the polymers to be recovered and reutilized in subsequent ATPS. This novel study on the CGTase recovery is not only to simplify the CGTase purification steps, but also to reduce the cost and environmental impact. The purified B. cereus CGTase with a YT of 87% and purification fold (PFT) of 13.1 was obtained from the EOPO/phosphate ATPS comprising TLL of 41.2% (w/w), VR of 1.25 and crude load of 20% (w/w) at pH of 7.0. Ionic liquids-based ATPS (ILATPS) was introduced as another ATPS approach for the purification of CGTase. Ionic liquids (ILs) were well known for their green properties in which they can be easily recycled, causing negligible impact to the environment. The rapid phase separation time and ability to enhance the biological activity of biomolecule has made the ILATPS an attractive purification method for CGTase. ILATPS was proved to be a better system for purification of CGTase which was able to purify B. cereus CGTase up to 13.9-fold with a YT of 96.2%. Another aim of the study was focus on the extractive bioconversion of CGTase using ATPS. PEG/dextran ATPS has been constructed and sago starch was used as the substrate in the starch bioconversion of CDs. Optimum recovery (13.7mg/mL) of CDs was achieved in PEG 20000/dextran T500 ATPS at TLL of 26.2% (w/w) with VR of 4.0, addition of 20% (w/w) crude CGTase and 6% (w/w) of sago starch. ATPS enabled the production and recovery of CDs in a single step by replenishment of substrate and phase components at a regular time interval. A dynamic model of this ATPS was implemented to understand and simplify the reaction kinetics of starch bioconversion by CGTase. The principal conclusion of this study was that ATPS has the potential to be practiced industrially for the recovery of CGTase and CDs for large scale productions and recoveries. In addition, the aqueous environment of ATPS provided a stable condition for the biological materials, which is well-suited as an extraction method for enzyme CGTase and CDs.